Legal support of the innovation development of the economy of the Republic of Belarus - Balashenko, Siarhei A.; Stepanenko, Dmitriy M. (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the research of mechanisms of the legislative support of the processes of the creation and introduction of innovations in the Republic of Belarus national economy. The current state of the innovation activity in the Belarusian economy is investigated. The offers for improving the Constitution of the Republic of Belarus in the context of its innovation development are formulated and substantiated. The expediency of consolidating at the legislative level the set of principles for the formation and realisation of the state innovation policy is proved. Measures for improving the venture capital financing of the innovation projects in the Republic of Belarus are proposed and substantiated.
Keywords: innovation; innovation activity; state; constitution; principle; venture capital financing; venture fund